1984
DOI: 10.1037/0022-3514.47.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Replicated item level factor analysis of the full MMPI.

Abstract: We completed a comprehensive factor analysis of the full MMPI item pool by using recent advances in computational facilities. Nearly 20,000 MMPI protocols were collected for the analysis, however, we discarded invalid records and protocols with more than 50 missing items. Analyses were computed on a developmental sample of 5,506 subjects and a cross-validation sample of 5,632. Twenty-one replicated factors were found by using an orthogonal varimax solution. The rotated factors were submitted to several experts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
121
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 3 publications
2
121
1
1
Order By: Relevance
“…Minnesota Multiphasic Personality Inventory (MMPI) (32) was administered, which consists of 566 true-false statements used to measure 10 clinical psychopathology scales, including neuroticism dimensions (33,34). To obtain a better neuroticism measure, 24 overlapping items similar to neuroticism were identified, which did not reflect phobias, health, health-related behaviours, or prevalent psychopathology (16).…”
Section: Participants Measures and Proceduresmentioning
confidence: 99%
“…Minnesota Multiphasic Personality Inventory (MMPI) (32) was administered, which consists of 566 true-false statements used to measure 10 clinical psychopathology scales, including neuroticism dimensions (33,34). To obtain a better neuroticism measure, 24 overlapping items similar to neuroticism were identified, which did not reflect phobias, health, health-related behaviours, or prevalent psychopathology (16).…”
Section: Participants Measures and Proceduresmentioning
confidence: 99%
“…Even large item pools may omit important aspects of personality. For example, McCrae, Costa, and Piedmont (1993) reported that there are relatively few items in the California Psychological Inventory that measure Agreeableness, and J. H. Johnson, Butcher, Null, and K. N. Johnson's (1984) item factor analysis of the Minnesota Multiphasic Personality Inventory (Hathaway & McKinley, 1983) found no factors related lo Conscientiousness.…”
Section: The Logic Of Domains and Facetsmentioning
confidence: 99%
“…This study utilized a sample of 1,567 patients referred to a medical center for coronary arteriography. A number of Varimax rotations were performed on a matrix computed from these data, including a 21-factor solution that was compared to that of Johnson et al (1984). Despite a very limited subject-to-variable ratio, Costa et al (1985) found reasonable correspondence with Johnson et al's (1984) factors for Neuroticism, Cynicism, Delinquency, Stereotypic Femininity, Stereotypic Masculinity, Phobias, and Dreaming.…”
mentioning
confidence: 95%
“…One of only two extant studies of the entire item matrix was completed by Johnson et al (1984). Subjects consisted of 11,130 patients who received treatment at Missouri Department of Mental Health facilities during the 1970s.…”
mentioning
confidence: 99%
See 1 more Smart Citation